Service Science, Management and Engineering Education for the 21st Century - Hefley, Bill; Murphy, Wendy (Service Science: Research and Innovations in the Service Economy, 2008)
Increasingly, academic and industrial leaders are recognizing that college graduates need new skills to address business and technical issues in a service business environment. Because services depend critically on people working together and with technology to provide value for others, these new skills include the ability to integrate across traditional disciplinary areas to obtain globally effective solutions. Service Science, Management and Engineering (SSME) is one such approach to properly focusing education and research on services, and to preparing tomorrow's graduates to work in an expanding services economy. Papers in this volume were developed from the 2006 conference hosted by IBM, Service Science, Management, and Engineering - Education for the 21st Century, designed to discuss the current status and foster the development and advancement of SSME. Contributions explore the ways SSME has been introduced into curricula, services research that is underway or is planned, and recommended actions for academia and governments to establish SSME as its own discipline. The book incorporates a variety of perspectives, informed by an international background in SSME experience and education, including management, business, social science, computer science and engineering. Advanced level computer science researchers and management professionals will benefit from the unique insight into the evolving field of SSME provided by this volume, and will derive an understanding of education needs and program offerings in SSME.